2018
DOI: 10.1097/iae.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

Residual Choroidal Vessels in Atrophy Can Masquerade as Choroidal Neovascularization on Optical Coherence Tomography Angiography

Abstract: The anterior displacement of larger choroidal vessels in atrophy requires clinician vigilance to avoid misinterpreting these vessels as CNV on en face OCTA. Our proposed postprocessing approach offers a potential solution to facilitate the interpretation of en face OCTA in these cases. In the absence of other tools, clinicians are encouraged to rely on the location of flow relative to Bruch membrane on cross-sectional OCTA flow images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…Another possibility could be that the choriocapillaris is completely obliterated in areas with RPD allowing us to visualize the flow in the underlying Sattler’s layer of medium sized choroidal vessels (manuscript in review). 44 All of these scenarios would likely result in hypoxia of the RPE and photoreceptors, and a reduction in the metabolic supply necessary for photoreceptor visual function. We hypothesize that this decrease in choriocapillaris perfusion is global in eyes with RPD explaining the correlation between visual acuity and non-perfusion of the choriocapillaris in these eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility could be that the choriocapillaris is completely obliterated in areas with RPD allowing us to visualize the flow in the underlying Sattler’s layer of medium sized choroidal vessels (manuscript in review). 44 All of these scenarios would likely result in hypoxia of the RPE and photoreceptors, and a reduction in the metabolic supply necessary for photoreceptor visual function. We hypothesize that this decrease in choriocapillaris perfusion is global in eyes with RPD explaining the correlation between visual acuity and non-perfusion of the choriocapillaris in these eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Flow signal in the B-scan has been shown to be crucial, as residual choroidal vessels in atrophy could mimic CNV and potentially confound these studies. 25 Studies further differed in the OCTA scan size used. It is plausible that smaller scans with higher scan density may be better at detecting the earliest subclinical CNV.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, artifacts includes segmentation, motion, blink, masking, unmasking, vessel doubling, and banding and out of window artifacts were demonstrated common in OCTA images, especially in eyes with pathology [ 10 ]. Furthermore, study showed that the anterior displacement of larger choroidal vessels in geographic atrophy could masquerade as choroidal neovascularization (CNV) on en face OCTA, so cross-sectional OCTA used in conjunction with en face OCTA was necessary for confirming the presence of CNV [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%